2021
DOI: 10.3390/children8080648
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Intravenous Sedation with Propofol in Non-Operating Room Anesthesia (NORA) for Dental Treatment in Uncooperative Paediatric Patients

Abstract: Background: Uncooperative children require sedative approach for dental treatment. The aim was to assess the effectiveness of Propofol in “Non-Operating Room Anesthesia” (NORA) for paediatric dental treatment; intraoperative side effects; postoperative side effects; post-discharge effects. Methods: a prospective study, involving 109 uncooperative children undergoing sedation in NORA using Propofol for dental treatment, was performed. Working sessions, success/failure, intraoperative and postoperative side effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…Our findings confirmed that propofol-based sedation could be used safely and effectively in young children who were unable to cooperate during dental procedures, consistent with the previous literature [8,[36][37][38]. The use of propofol has become increasingly popular for moderate-to-deep sedation in office-based procedures over the past few decades.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings confirmed that propofol-based sedation could be used safely and effectively in young children who were unable to cooperate during dental procedures, consistent with the previous literature [8,[36][37][38]. The use of propofol has become increasingly popular for moderate-to-deep sedation in office-based procedures over the past few decades.…”
Section: Discussionsupporting
confidence: 91%
“…Respiratory problems are the most reported side effects in children undergoing intravenous sedation (5.5–31.7%). 23 Herein, a decrease of blood oxygen saturation was observed in 12.6% (43/342) of cases; however, all recovered within 30 s. The lowest pulse oximetry readings of 7 children were below 70%, the lowest of which was 52% in one case who required face mask oxygen, while the others recovered after the operation was stopped and a jaw thrust performed. The AAP have suggested that the vast majority of sedation complications can be managed with simple methods, such as supplemental oxygen provision, airway opening, suctioning, oral or nasopharyngeal airway placement, and bag-mask-valve ventilation.…”
Section: Discussionmentioning
confidence: 82%
“…In the event oxygen desaturation, the patient needs oxygen administration and removal of the rubber dam may delay this maneuver, and that the oropharynx could not be cleaned easily. 23 , 25 We used a rubber dam in most of the procedures, especially those which would produce a greater quantity of water mist, as the rubber dam isolates most of the exogenous water, avoiding the accumulation thereof in the oropharynx, and reduces the occurrence of cough. Furthermore, when breathing problems occurred, we found that removing the rubber dam did not impact the anesthetist's ability to institute emergency treatment.…”
Section: Discussionmentioning
confidence: 99%
“…N 2 O was a self-administered inhaled gas reserved in a pre-prepared cylinder and trained nurses can conduct without the presence of professional anesthesiologists. Its action is rapid and reversible after stopping inhalation and N 2 O has no depressive effects on the respiratory or cardiovascular function [ 40 ], and does not obscure the signs and symptoms that may be necessary for disease diagnosis. The mixture of 20% N 2 O and 80% oxygen has an equivalent analgesic effect as well as a good sedative effect with 15 mg morphine [ 41 ].…”
Section: Discussionmentioning
confidence: 99%